2020
DOI: 10.3390/ijerph17186520
|View full text |Cite
|
Sign up to set email alerts
|

Polycycl. Aromatic Hydrocarbon Exposure of Children in Typical Household Coal Combustion Environments: Seasonal Variations, Sources, and Carcinogenic Risks

Abstract: Polycyclic aromatic hydrocarbon (PAH) emissions from the combustion of household solid coal for cooking and heating cause great harm to public health in China, especially in less developed areas. Children are one of the most susceptible population groups at risk of indoor air pollutants due to their immature respiratory and immune systems. However, information on PAH exposure of children is limited due to limited monitoring data. In this study, we aimed to assess the seasonal differences of PAHs in classrooms,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 44 publications
0
11
0
1
Order By: Relevance
“…All of the sampled variables were sampled randomly and independently. The information on variable distributions was taken from Chen and Lia [ 17 ] and Liu et al [ 18 ]. We sampled the TCP from our own data after log-transforming them, separately for warm and cold seasons.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All of the sampled variables were sampled randomly and independently. The information on variable distributions was taken from Chen and Lia [ 17 ] and Liu et al [ 18 ]. We sampled the TCP from our own data after log-transforming them, separately for warm and cold seasons.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study by Yang et al [ 15 ] found that both PM 1 and PM 2.5 levels were associated with poorer lung function in children, with stronger associations for PM 1 compared to PM 2.5 , pointing to the importance of regulating finer PM fractions. Furthermore, a lot of previous health risk estimations were carried out taking into account larger fractions of particulate matter (PM 10 or even total suspended particles), which do not enter deeply into the respiratory system [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, Monte Carlo simulation with 10,000 iterations was employed in this study to appraise the probabilistic ILCR range of children exposed to PAHs for the exposed and comparative schools. The simulation also integrated the uncertainty and variability of the measured PAH concentrations and the specific determinant of children’s exposure [ 47 , 50 , 51 ]. Afterwards, sensitivity analysis was conducted to identify input parameters that significantly influence the estimated risk.…”
Section: Methodsmentioning
confidence: 99%
“…It was also found that household solid fuel use is associated with an increased stroke risk [39]. Indoor coal combustion processes are known for their contribution to the generation of highly hazardous PAH [40,41].…”
Section: Discussionmentioning
confidence: 99%